Approaches to Improving the Effectiveness of Forensic Tactical Operations Implemented During Pre-Trial Investigation of Man-Made Accidents in The Republic of Kazakhstan - TEMIRGAZIN, Roman Khurmatullaevich (Journal of Advanced Research in Law and Economics, 2018)
The article substantiates the relevance of effective methods to improve tactical operations for investigation of industrial disasters, taking into account the ever increasing harmful impact of man-made accidents and aggravated consequences of their impact on national security in the Republic of Kazakhstan (RK). The research is aimed at the development of a set of practical measures to improve the effectiveness of forensic pre-trial investigation of man-made accidents. By means of logical semantics method, the essence of the concept of emergency man-made situations has been clarified. A differentiated approach to understanding the legal nature of emergency situations of anthropogenic nature has been substantiated. Features of pre-trial investigation of man-made accidents as destructive factors of their legal classification have been revealed and substantiated. Approaches to amending the Criminal Code of the Republic of Kazakhstan on initiation of pre-trial investigation into a criminal case and a pre-trial investigation with the aim to establish the true causes of man-made incidents have been substantiated. An algorithm for modifying the Mindmap method in the practice of forensic tactical operations during the investigation of man-made accidents has been argued and presented. A structural and logical model has been developed to improve the criminal pre-trial investigation of man-made accidents in Kazakhstan.